MEMAJUKAN KEAMANAN MARITIM PADA SEKTOR KESELAMATAN LAUT DALAM MENGHADAPI PENYEBARAN COVID-19 - Kasta Rosyada; Agung Imam Zulhatta; Marsetio Marsetio (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2020)
The development of the spread of the corona virus or Covid-19 has risen to become a constellation of global problems and put the world in unpredictable situations. One of the efforts made to slow down the spread and mitigate the impact is by limiting and closing access crossings both locally and internationally. This affects the transportation network, one of which is the closure of ports and the rejection of ship arrivals. In fact when this phenomenon occurs, the role of humanitarian services and seafarers is very important in delivering vital logistics and includes the supply of basic health equipment which is the primary need in responding to and resolving the Covid-19 Pandemic. This paper will discuss the importance of maintaining marine safety at sea and protection of the marine environment and maintaining the stability of the movement of economic activity at sea from the effects caused by the global covid-19 pandemic.